A Confidence-Based Assessment Method for Distinguishing Pyroclastic Density Current Deposits From Other Volcaniclastic Units - Cowlyn, James; Kennedy, Ben M.; Gravley, Darren M.; Cronin, Shane J. (Frontiers in Earth Science, 2020)
Pyroclastic density currents (PDCs) are a destructive volcanic hazard. Quantifying the types, frequency and magnitudes of PDC events is essential for effective risk management, but since historical records at best extend a few hundred years this usually relies on identifying deposits in the geological record. However, small volume unconsolidated PDC deposits have low preservation potential and can be difficult to distinguish from other volcaniclastic units, especially in proximal locations. Consequently many small or poorly exposed deposits can be overlooked. Here, we introduce a structured field method for assessing volcaniclastic deposits of unknown origin with a particular focus on identifying deposits from concentrated PDCs (pyroclastic flows). The method differs from traditional identification schemes in that it does not uniquely attribute a deposit to a single depositional process, but instead assesses how confidently different volcaniclastic processes could explain the observed deposit features. Therefore, the underlying uncertainties in the assessment are explicitly addressed. The method allows consistent, rapid assessment of candidate pyroclastic flow deposits in the field, and the concept could easily be adapted for assessing other types of volcaniclastic deposit. The introduction of confidence levels in deposit interpretations should be useful for carrying though uncertainties into probabilistic assessments of volcanic hazards.